Therapy landscape in patients with metastatic HER2-positive breast cancer: data from the PRAEGNANT real-world breast cancer registry - Lux, Michael Patrick; Wallwiener, Markus; Schneeweiss, Andreas (Cancers, 2019)
This study presents comprehensive real-world data on the use of anti-human epidermal growth factor receptor 2 (HER2) therapies in patients with HER2-positive metastatic breast cancer (MBC). Specifically, it describes therapy patterns with trastuzumab (H), pertuzumab + trastuzumab (PH), lapatinib (L), and trastuzumab emtansine (T-DM1). The PRAEGNANT study is a real-time, real-world registry for MBC patients. All therapy lines are documented. This analysis describes the utilization of anti-HER2 therapies as well as therapy sequences. Among 1936 patients in PRAEGNANT, 451 were HER2-positive (23.3%). In the analysis set (417 patients), 53% of whom were included in PRAEGNANT in the first-line setting, 241 were treated with H, 237 with PH, 85 with L, and 125 with T-DM1 during the course of their therapies. The sequence PH → T-DM1 was administered in 51 patients. Higher Eastern Cooperative Oncology Group (ECOG) scores, negative hormone receptor status, and visceral or brain metastases were associated with more frequent use of this therapy sequence. Most patients received T-DM1 after treatment with pertuzumab. Both novel therapies (PH and T-DM1) are utilized in a high proportion of HER2-positive breast cancer patients. As most patients receive T-DM1 after PH, real-world data may help to clarify whether the efficacy of this sequence is similar to that in the approval study.
Published: 21 December 2018
Gesehen am 04.06.2019